Analisis Kebutuhan Pengembangan E-LKPD Berbasis Pendekatan Deep Learning pada Pelajaran Matematika untuk Siswa Sekolah Dasar - Devy Sefiana Putri; Neza Agusdianita; Agus Susanta; Nurlita Anjani; Anisa Putri Listari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the needs in the development of E-LKPD based on the Deep Learning approach in mathematics learning for students of SDN 45 Bengkulu City, where the challenges in mathematics lessons are mainly found in the low critical thinking skills of students in elementary school. The method used is Research and Development (R&D) with the ADDIE model, which consists of five stages, namely: analysis, design, development, implementation and evaluation. However, in this study, it only used the analysis stage and also through interviews with classroom teachers. Data was collected through a questionnaire involving 17 students and classroom teachers to get students' perceptions of the importance of critical thinking skills and teaching materials, especially LKPD available in schools. The results of the study show that there is a gap in the quality and relevance of teaching materials, especially LKPD, as well as the need for additional teaching materials, especially in student worksheets that are responsive to the needs of students who are very important in mathematics lessons, as well as creating students who are more in-depth in understanding mathematics lessons.